Exploring the Neurophysiological Basis of Electroacupuncture in the Treatment of Cardiovascular-related Diseases: Vagal Interoceptive Loops - Yun Liu; Tiancheng Xu; Zhi Yu; Bin Xu (Medical Science: Trends and Innovations Vol. 5, 2025)
The vagal sensory neuron (VSN) is an essential interoceptive pathway that is connected to every level of the body. Its intricate genetic coding provides sustenance for physiological processes including controlling blood pressure and respiration. Electroacupuncture (EA) is a proven surface stimulation therapy that can regulate vagal nerve activity, which can effectively prevent cardiovascular diseases. The majority of existing EA clinical trials in cardiovascular-related disorders are modest nonmulticenter clinical trials, and no large-scale EA clinical trials for cardiovascular-related diseases have been reported, with only a few research studies on effective acupuncture point selection based on biological effects and causes. A growing number of studies have concentrated on the mapping of VSN codes, but little is known and the physiological background of how EA influences interoceptive has not been fully explored. Here, prior research on the mechanisms of action of EA, VSNs, and heart is reviewed, aiming to explore the potential interconnections among these three areas, i.e., possible interoceptive loops. This analysis is intended to propose novel research strategies for utilizing EA to modulate vagal interoceptive, thereby improving cardiac performance. At first, the major role of vagal nerve fibers in the control of cardiac activity is clarified. Furthermore, the complex projection patterns of VSNs across various visceral tissue levels are also clarified, which facilitates the perception of diverse stimuli and functional adaptations. The study also revealed that targeted control of multimodal interoceptive is essential for synchronizing cardiovascular function. A strategy is proposed in which the EA of the VSNs is employed to activate the interoceptive loop and reduce the risk of cardiovascular disease. Further research studies could focus on the genetic coding of VSNs could lead to the augmented comprehension of individual afferent or efferent neural pathways and more effective therapeutic approaches for treating illnesses.